Irrigation Differentially Impacts Populations of Indigenous Antibiotic-Producing Pseudomonas spp. in the Rhizosphere of Wheat - Mavrodi, Olga V. (American Society for Microbiology, 2012)
This work determined the impact of irrigation on the seasonal dynamics of populations of Pseudomonas spp. producing the antibiotics phenazine-1-carboxylic acid (Phz(+)) and 2,4-diacetylphloroglucinol (Phl(+)) in the rhizosphere of wheat grown in the low-precipitation zone (150 to 300 mm annually) of the Columbia Plateau of the Inland Pacific Northwest. Population sizes and plant colonization frequencies of Phz(+) and Phl(+) Pseudomonas spp. were determined in winter and spring wheat collected during the growing seasons from 2008 to 2009 from selected commercial dryland and irrigated fields in central Washington State. Only Phz(+) bacteria were detected on dryland winter wheat, with populations ranging from 4.8 to 6.3 log CFU g(−1) of root and rhizosphere colonization frequencies of 67 to 100%. The ranges of population densities of Phl(+) and Phz(+) Pseudomonas spp. recovered from wheat grown under irrigation were similar, but 58 to 100% of root systems were colonized by Phl(+) bacteria whereas only 8 to 50% of plants harbored Phz(+) bacteria. In addition, Phz(+) Pseudomonas spp. were abundant in the rhizosphere of native plant species growing in nonirrigated areas adjacent to the sampled dryland wheat fields. This is the first report that documents the impact of irrigation on indigenous populations of two closely related groups of antibiotic-producing pseudomonads that coinhabit the rhizosphere of an economically important cereal crop. These results demonstrate how crop management practices can influence indigenous populations of antibiotic-producing pseudomonads with the capacity to suppress soilborne diseases of wheat.